Variable Presentations of Tuberculosis during COVID-19 Pandemic- A Case Series (Journal of Medicine, 2021)
Tuberculosis is an ancient infectious disease, which can involve almost any organ of the body and can have broad spectrum of presentations. The objective of this case series presentation is to highlight the importance of considering Tuberculosis as a diagnosis even in this COVID pandemic time. It presents with wide variety of clinical features involving different organs and often potentially fatal. Mortality from tuberculosis is most often due to delay in diagnosis & thus starting treatment. Thus, treatment should be initiated immediately based on strong clinical suspicion. Here we have presented six different cases of TB where each case presented differently in a tertiary care private hospital of Dhaka.J MEDICINE JAN 2021; 22 (1) : 60-66